Health service use before and after dementia diagnosis: a retrospective matched case–control study. Issue 11 (25th November 2022) - Kosteniuk, Julie; Osman, Beliz Açan; Osman, Meric; Quail, Jacqueline M; Islam, Naorin; O'Connell, Megan E; Kirk, Andrew; Stewart, Norma J; Morgan, Debra
Abstract : Objectives: This study investigated patterns in health service usage among older adults with dementia and matched controls over a 10-year span from 5 years before until 5 years after diagnosis. Design: Population-based retrospective matched case–control study. Setting: Administrative health data of individuals in Saskatchewan, Canada from 1 April 2008 to 31 March 2019. Participants: The study included 2024 adults aged 65 years and older living in the community at the time of dementia diagnosis from 1 April 2013 to 31 March 2014, matched 1:1 to individuals without a dementia diagnosis on age group, sex, rural versus urban residence, geographical region and comorbidity. Outcome measures: For each 5-year period before and after diagnosis, we examined usage of health services each year including family physician (FP) visits, specialist visits, hospital admissions, all-type prescription drug dispensations and short-term care admissions. We used negative binomial regression to estimate the effect of dementia on yearly average health service utilisation adjusting for sex, age group, rural versus urban residence, geographical region, 1 year prior health service use and comorbidity. Results: Adjusted findings demonstrated that 5 years before diagnosis, usage of all health services except hospitalisation was lower among persons with dementia than persons without dementia (all p<0.001). After this point, differences in higher health service usage among persons with dementia compared to without dementia were greatest in the year before and year after diagnosis. In the year before diagnosis, specialist visits were 59.7% higher (p<0.001) and hospitalisations 90.5% higher (p<0.001). In the year after diagnosis, FP visits were 70.0% higher (p<0.001) and all-type drug prescriptions 29.1% higher (p<0.001). Conclusions: Findings suggest the year before and year after diagnosis offer multiple opportunities to implement quality supports. FPs are integral to dementia care and require effective resources to properly serve this population.